Indian agricultural statistics
Volumes for 1939/40-42/43--1943/44-46/47 in 2 v.: v. 1 contains data for the Indian provinces; v. 2, for the Indian states. volumes for 1947/48-48/49- in 2 v.: v. 1, Summary tables; v. 2, Detailed tables.